The Role of Multicultural Competence Based on Local Wisdom in the Cross-Cultural Adaptation Javanese Muslim Minority in Pagayaman Village, Buleleng Regency, Bali Province - Bherta Sri Eko Murtiningsih; Veronika Veronika (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
The cross-cultural adaptation in different ethnic and religious communities is not an easy process. Stereotype factors, prejudice, and ethnocentrism will affect the process. In most cases, the cross-cultural adaptation process cannot be optimal and cause psychological pressure and disharmonious interactions between immigrants and hosts. However, the Javanese-Muslim Pagayaman and Balinese Hindus can adapt well. The success of the cross-cultural adaptation is supported by the cultural competence and local wisdom of the two communities. This study aims to determine the cultural competence and local wisdom of Javanese-Muslim Pagayaman and Balinese Hindus in the village of Pagayaman located in Buleleng Regency, Bali Province, during the cross-cultural adaptation process. The study uses the theory of cultural adaptation from Young Yun Kim and a qualitative approach and case study methods from Robert K Yin. Research participants are community and religious leaders. The findings show that the adaptation model performed by both Balinese Hindus and Pagayaman Muslims is integration. Successful adaptation is supported by cultural competencies such as respect (valuing other cultures,Â  cultural diversity), openness (to intercultural learning and people from other cultures, withholding judgment), curiosity, and discovery (tolerating ambiguity and uncertainty).